Political Determinants of Tax Policy: Evidence from the Canadian Provinces - King, Marshall (Université d'Ottawa | University of Ottawa, 2011)
This paper uses the methodology presented in Ashworth and Heyndels (2002) and Lucinda and Arvate (2007) to test for the significance of opportunistic and partisan budget cycling within Canadian provincial tax data. The results of the empirical analysis su